THE SELECT METHOD OF ITERATION TARGET SPECTRUM FOR INDOOR ROAD SIMULATION TEST - ZHENG SongLin; DENG Xin; FENG Jinzhi; ZHAO LiHui; YU JiaWei (Jixie qiangdu)
How to select the appropriate target spectrum for iterative test is a key point to vehicle indoor road simulation testing,The conventional selecting method is to select the median fatigue damage spectrum as the target spectrum. Therefore,the method of selecting the minimum standard deviation spectrum as the target spectrum is introduced in this paper based on the load spectrum measured in proving ground. To verify the validness of this methodology,analyses and comparison between the two methods are conducted from numerical statistical analysis,rain-flow cycle damage distribution,shock response spectrum and fatigue damage spectrum. The results indicate that the minimum standard deviation spectrum is better than the median fatigue damage spectrum. Finally,the result of vehicle indoor road simulation test shows the methodology is right.